How low can you go? Antibiotic use in Swedish dogs with gastroenteritis - Ljungquist, Ditte; Andersson, Anna-Maria; Johansson, Emelia; Tham, Johan; Toresson, Linda (Frontiers in Veterinary Science, 2024)
BackgroundCanine gastroenteritis (CGE) is a common cause for seeking veterinary care in companion animal medicine and an area where antibiotics have been reported to be widely used. Therefore, creating relevant benchmarks for antibiotic use in CGE is important when implementing and analyzing antibiotic stewardship interventions. The aim of this paper was to describe the level and temporal trend of systemic antibiotic use for CGE in Sweden between 2020 and 2023.Materials and methodsThis was an observational multicenter cohort study. Retrospective data from 93,641 CGE consultations was extracted from the electronic health record and analyzed. All CGE consultations were included irrespective of age, breed, severity of disease and level of care. To evaluate the data, 100 medical records of CGE consultations were also manually reviewed using a predefined study protocol.ResultsThe overall level of systemic antibiotic use in Swedish dogs diagnosed with gastroenteritis was 5.7% during the study period, with aminopenicillins being the most abundantly used antibiotics (60.2%). The yearly level of antibiotic use in CGE declined from 8.1% in 2020 to 3.9% in 2023, with a statistically significant annual percentage change (APC) of −21.3% (95% CI, −22.8 to −19.7). Concurrently, the annual all-cause mortality decreased for all CGE consultations. Higher levels of antibiotic use were seen in hospitalized CGE (21.7% compared to 2.1% for non-hospitalized CGE, OR 13.1, 95% CI: 12.3–14.0, p < 0.001) and hemorrhagic diarrhetic CGE (21.0% compared to 5.5% for non-hemorrhagic diarrhetic CGE, OR 4.6, 95% CI: 4.2–4.9, p < 0.001).ConclusionThis study revealed a low level and a significantly declining trend of antibiotic use in canine gastroenteritis in Sweden, implicating a high level of awareness and compliance to antibiotic guidelines among Swedish veterinarians. During the same period, the all-cause mortality rates decreased significantly for all CGE consultations, implicating that this level of antibiotic use do not compromise patient safety. Benefiting from automatic surveillance, we hereby provide important benchmarks which should encourage more prudent use of antibiotics in CGE internationally.